PENERAPAN MODEL PEMBELAJARAN KONTRUKTIVISTIK DENGAN MEDIA ALAT PERAGA UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF SISWA KELAS V SDN PIYANGGANG 02 - Virdinarti Putra, Lisa (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The purpose of this study was to determine whether or not there was a difference in cognitive abilities between students who received contructivistic learning with teaching aids media, with students who received expository learning models; Mathematical cognitive abilities of students who received contructivistic learning with teaching aids media were better or not than students who received expository learning in grade 5 students at Piyanggang Elementary School 02. This type of research is True Experimental Design using a randomized research design on objects. The population in this study were all fifth grade students of SDN Piyanggang 02 Semarang Regency in the 2017/2018 school year with 28 students divided into two classes. The sample in this study was taken by cluster random sampling and selected class V B students as the experimental class and class V A students as the control class using the expository learning model. The research data was obtained by test and documentation methods. The results of data analysis with different tests of cognitive abilities between the experimental class and the control class showed that the average value in the experimental class was higher than the average value in the control class. The average value of the experimental class is 81 while the average value of the control class is 69. This shows that learning with the contructivistic model with media teaching aids proves to be better than expository learning in the control class.